Understanding The Role of Microbial Metabolites in Heart Failure Pathogenesis - Putu Gizha Satrya Gautama (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The gut-heart axis represents a critical pathway linking gut microbiota to cardiovascular health. In heart failure (HF), gut dysbiosis and altered microbial metabolites are thought to contribute to systemic inflammation and metabolic disturbances that may accelerate disease progression. This narrative review summarizes current clinical and experimental evidence on gut dysbiosis and key microbial metabolites, and their mechanistic roles in HF pathogenesis. In patients with HF, microbial diversity is reduced, characterized by a depletion of anti-inflammatory taxa, and an overrepresentation of pro-inflammatory species. These compositional shifts also alter the concentration of microbial metabolites. For example, trimethylamine N-oxide level is elevated and associated with myocardial fibrosis and endothelial dysfunction, while short-chain fatty acids that exert anti-inflammatory effects and help preserve gut barrier integrity, are reduce. Other microbial metabolites also contribute to HF pathogenesis through distinct mechanism. Intestinal hypoperfusion in HF further increases gut permeability, facilitating the translocation of microbes and microbial metabolites, and triggering systemic inflammation. These alterations correlate with HF severity, prognosis, and clinical outcomes. Understanding the gut-heart axis, gut dysbiosis, and specific microbial metabolites may open new avenues for diagnosis and treatment in HF. Further research is needed to validate these mechanisms and assess the potential of microbiota-targeted therapies.